Communicative skills development using interactive technologies - Ekaterina A. Gorlova; Marina O. Polukhina; Ol’ga V. Ershova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper considers one of the most important technologies in teaching Russian as a foreign language - interactive learning. The use of this technology helps to increase the effectiveness of training and the development of students' motivation, as it is aimed at realizing the main goal, which is to enhance speaking competence, using dialogue forms of communication in each lesson. The paper describes examples of interactive learning technologies that can be used when teaching Russian as a foreign language. However, the authors of the paper believe that it is not possible to make the process fully interactive in the modern context due to the lack of both technical equipment and a complete educational and methodological complex. The authors see a partial solution to this problem in the creation and further use of authentic materials. This didactic technique allows you to increase interest in the subject under study, to form and develop both linguoculturological and communicative competencies. This paper presents an authentic set of interactive teaching tasks developed by the authors for the Russian as a foreign language lesson. The lesson plan is shown, and the results of introducing the technology are described using the example of separate exercises. Having implemented the lesson plan, the authors have come to certain conclusions. So, for example, based on the active participation of students and the interest shown in the topic of the lesson, the authors believe that the language material was chosen successfully. The motivation of students plays a vital role in the acquiring of educational material, and therefore in the development of communicative competence.